INNOVATIVE APPROACHES TO FORMING AN ENTREPRENEURIAL ENVIRONMENT IN RURAL COMMUNITIES - TOMASHUK, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines modern innovative approaches to the formation of a favorable business environment in rural communities of Ukraine in the context of socio-economic transformations, decentralization and wartime. The relevance of activating entrepreneurial initiative at the local level as an important tool for ensuring employment, increasing incomes of the population and sustainable development of territories is substantiated. The study analyzes the factors that determine the dynamics and quality of entrepreneurship development in rural areas, in particular, infrastructure, financial, institutional and educational aspects. Special attention is paid to barriers that hinder the development of small and medium-sized businesses in communities, and the role of local government in creating a favorable business climate is also highlighted. Innovative approaches to stimulating entrepreneurial activity are proposed, including the digitalization of business support services, the creation of agricultural clusters, the development of social entrepreneurship, the use of crowdfunding platforms and microfinancing instruments. Based on the analysis of the best Ukrainian and foreign practices, a model of multi-level support for entrepreneurship in rural areas is presented, taking into account local specifics. Ways to improve the policy of rural entrepreneurship development are proposed. Prospects for integrating rural entrepreneurship into the strategic planning of communities are presented. As a result, a set of practical recommendations has been formulated to improve the policy of supporting entrepreneurial activity in rural areas, in particular through the development of partnerships between authorities, business and civil society, the implementation of business education programs and advisory support for entrepreneurs. The results obtained can be used in the development of strategies for the socio-economic development of communities, the improvement of state and regional policies for promoting entrepreneurship, as well as in scientific research on the problems of rural development and the economics of entrepreneurship.